2015
DOI: 10.1007/s00414-015-1257-4
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution mass spectrometric determination of the synthetic cannabinoids MAM-2201, AM-2201, AM-2232, and their metabolites in postmortem plasma and urine by LC/Q-TOFMS

Abstract: High-resolution mass spectrometry and accurate mass measurement by liquid chromatography/quadrupole-time of flight mass spectrometry (LC/Q-TOFMS) was applied to postmortem plasma and urine specimens from an autopsy of a fatal case involving synthetic cannabinoid use, resulting in the detection of three synthetic cannabinoids: MAM-2201, AM-1220, and AM-2232. We searched for their metabolites existing in postmortem plasma or urine by LC/Q-TOFMS and were able to detect N-dealkylated metabolites, defluorinated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…plasma concentrations ranged from <0.1 to 49 ng/mL, indicating its extensive metabolism [19][20][21][25][26][27]. N-(5-hydroxypentyl)-MAM-2201, N-(4-hydroxyfluoropentyl)-MAM-2201, MAM-2201 pentanoic acid, and dealkyl-MAM-2201 have been identified as the metabolites of MAM-2201 in urine and hair samples from MAM-2201 abusers [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%
“…plasma concentrations ranged from <0.1 to 49 ng/mL, indicating its extensive metabolism [19][20][21][25][26][27]. N-(5-hydroxypentyl)-MAM-2201, N-(4-hydroxyfluoropentyl)-MAM-2201, MAM-2201 pentanoic acid, and dealkyl-MAM-2201 have been identified as the metabolites of MAM-2201 in urine and hair samples from MAM-2201 abusers [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%
“…QTOF HRMS quantification of the three synthetic cannabinoids MAM-2201, AM-1220, and AM-2232 in postmortem plasma and urine specimens was described by Zaitsu et al in the context of a case report (Zaitsu et al 2015). They also searched for plasma and urine metabolites and were able to detect N-dealkylated metabolites of AM-1220 and AM-2232 and defluorinated and further oxidized metabolites of MAM-2201.…”
Section: Multi-analyte Lc-hrms Approaches For Quantification Of Doamentioning
confidence: 99%
“…Furthermore, metabolism studies generally offer information on the CID pathways of NPS analogues since it is a conventional practice to determine the CID pathways of the parent molecule in order to identify the locations of metabolic transformations [48,[89][90][91][92][93][94][95][96][97]. As mentioned previously, the efficacy of bottom-up approaches largely relies on the acquisition of MS/MS and it has been suggested that DIA techniques should be used rather than DDA [86].…”
Section: Bottom-up Non-targeted Screeningmentioning
confidence: 99%
“…LC has been the most commonly adopted conventional separation technique coupled to HRMS for the analysis of NPS due to the well-recognized fact that analytes of interest do not need to be volatile and do not require derivatization [15,28,30,33,39,42,43,[46][47][48].…”
Section: Conventional Separation Techniques Coupled To Hrmsmentioning
confidence: 99%